2022
DOI: 10.3390/chemosensors10120525
|View full text |Cite
|
Sign up to set email alerts
|

Room-Temperature NO2 Gas Sensors Based on Granulated Carbon Nanofiber Material

Abstract: Room-temperature gas sensors based on granulated carbon nanofiber material were investigated for the detection of NO2. The granulated material consisting of intertwined carbon nanofibers was synthesized by the decomposition of CH4 over the Ni/Al2O3 catalyst in a vibro-fluidized bed reactor. Carbon material was investigated using transmission electron microscopy, Raman spectroscopy, low-temperature nitrogen adsorption, and X-ray photoelectron spectroscopy. Investigation of the gas sensors towards NO2 at room te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 77 publications
0
0
0
Order By: Relevance
“…The enthalpy of adsorption increased for the set from CNFs-1 to CNFs-5 samples. Previously, we have found that the granulated carbon nanofiber material, synthesized over Ni/Al 2 O 3 catalyst obtained by coprecipitation technique and synthesized at 1 atm and 550 • C, has also shown the physical nature of NO 2 adsorption [34]. However, the enthalpy of adsorption in [34] was 2-5 times of magnitude higher compared to CNFs studied in this paper.…”
Section: Adsorption Isothermsmentioning
confidence: 53%
See 4 more Smart Citations
“…The enthalpy of adsorption increased for the set from CNFs-1 to CNFs-5 samples. Previously, we have found that the granulated carbon nanofiber material, synthesized over Ni/Al 2 O 3 catalyst obtained by coprecipitation technique and synthesized at 1 atm and 550 • C, has also shown the physical nature of NO 2 adsorption [34]. However, the enthalpy of adsorption in [34] was 2-5 times of magnitude higher compared to CNFs studied in this paper.…”
Section: Adsorption Isothermsmentioning
confidence: 53%
“…Previously, we have found that the granulated carbon nanofiber material, synthesized over Ni/Al 2 O 3 catalyst obtained by coprecipitation technique and synthesized at 1 atm and 550 • C, has also shown the physical nature of NO 2 adsorption [34]. However, the enthalpy of adsorption in [34] was 2-5 times of magnitude higher compared to CNFs studied in this paper. Apparently, this is caused by the higher disorder degree of CNFs investigated in this paper (according to Raman spectroscopy I(D)/I(G) was 1.69-2.0 compared to 0.98 for granulated CNF in [34]).…”
Section: Adsorption Isothermsmentioning
confidence: 53%
See 3 more Smart Citations